Studi komparasi model mind mapping dan think pair share terhadap keterampilan berpikir kreatif ditinjau dari minat membaca siswa kelas IV sekolah dasar - Etviana, Riesda; Poerwanti, Jenny Indrastoeti Siti; Wahyuningsih, Siti (Didaktika Dwija Indria, 2021)
The purpose of this research is knowing the differences between (1) Mind Mapping learning model and Think Pair Share learning model toward student creative thinking skill, (2) reading interest effect of high and low groups towards students creative thinking skills, and (3) interaction effect of learning models and reading interest towards student creative thinking skill. The population was fourth grade’s students at elementary school in Puncu Region. The samples had chosen through Cluster Random Sampling and there are two schools that researcher had chosen, they are SD N Gadungan 2 and SD N Gadungan 5. This research used experimental method and the data were analyzed with Two Way Anova Test using SPSS 16.0 programme. The data were taken from the result of creative thinking skill esay tests and student’s reading interest questionnaire. The result showed that, first there was differences between Mind Mapping and Think Pair Share learning model towards students creative thinking skill (Sig. = 0,00 < α = 0,05). Second, there was differences between high reading interest and low reading interest towards students creative thinking skill (Sig. = 0,00 < α = 0,05). Third, there was no interaction between learning model and reading interest towards students creative thinking skill (Sig. = 0,935 > α = 0,05).